1996
DOI: 10.1038/bjc.1996.329
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical vs guaiac faecal occult blood tests in a population-based screening programme for colorectal cancer

Abstract: Summary Two faecal occult blood tests (FOBTs), Hemoccult II (guaiac based) and Hemeselect (immunochemical) were compared in a population screening for colorectal cancer on 24 282 subjects aged 40-70. Hemeselect was interpreted according to a lower (+ and +) and a higher (+) positivity threshold. A total of 8008 compliers were enrolled in the study. Positivity rates: Hemoccult=6.0%, Hemeselect (+ and ±) = 8.2%, Hemeselect (+) = 3. 1%. Among FOBT-positive subjects complying with the diagnostic work-up, 22 had co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 10 publications
3
43
0
4
Order By: Relevance
“…This, combined with the association of Hb content with adenoma characteristics, and with the adoption of a 100 ng ml À1 Hb positivity threshold, allowed for a favourable advanced/not advanced adenoma ratio of approximately 3 : 1 (669/221), as compared to approximately 1 : 1 when guaiac FOBT was employed (Castiglione, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This, combined with the association of Hb content with adenoma characteristics, and with the adoption of a 100 ng ml À1 Hb positivity threshold, allowed for a favourable advanced/not advanced adenoma ratio of approximately 3 : 1 (669/221), as compared to approximately 1 : 1 when guaiac FOBT was employed (Castiglione, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The detailed features of the screening programme, inviting residents in the 50 -70 years age group to biennial FOBT, have been described elsewhere (Castiglione et al, 1996(Castiglione et al, , 2000Zappa et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On top of that, utilization of either immunochemical or guaiac FOBT could have attributed to difference in positivity rate between all of the studies aforementioned. Immunochemical FOBT was found to be more superior than guaiac FOBT (Castiglione et al, 1996;Launoy et al, 2005). The aforementioned studies in England (Moss et al, 2011;Logan et al, 2012), Scotland and France (Leuraud et al, 2013) were utilizing guaiac as compared to immunochemical FOBT was used in Japan (Oono et al, 2010) and our study.…”
Section: Discussionmentioning
confidence: 94%
“…In a recent review, the sensitivity of FOBT using guaiac-based tests for CRC detection was reported as 26% in asymptomatic nonreferred populations (33). IFOBTs were recommended for CRC screening due to the higher sensitivity than guaiac-based tests (7,(34)(35)(36). In fact, a single IFOBT was reported to have 65.8% sensitivity for detecting invasive CRC (37).…”
Section: Discussionmentioning
confidence: 99%